Nano/Microcarriers in Drug Delivery: Moving the Timeline to Contemporary - Nikezić, Ana Vujačić; Novaković, Jasmina Grbović (Current Medicinal Chemistry, 2023)
Treatment of various diseases, especially cancer treatment, includes the potential use of different types of nanoparticles and nanostructures as drug carriers. However, searching for less toxic and more efficient therapy requires further progress, wherein recent developments in medicine increasingly include the use of various advanced nanostructures. Their more successful application might be achieved by leveling imbalances between the potentiality of different nanostructures and the demands required for their safe use. Biocompatibility, biodegradability, prolonged circulation time and enhanced accumulation and uptake by cells are some of the key preconditions for their usage in efficient drug delivery. Thanks to their greatly tunable functions, they are major building blocks for manufacturing novel materials. Nevertheless, given that their toxicity is questionable, their practical application is challenging. Hereof, before entering the sphere of human consumption, it is of critical importance to perform more studies regarding their toxicity and drug distribution. This review emphasizes recent advances in nanomedicine, employing different kinds of conventionally used nanoparticles as well as novel nanoparticles and nanostructures. Special emphasis is placed on micro/nanomotors (MNMs), discussing their opportunities, limitations, challenges and possible applications in drug delivery and outlining some perspectives in the nanomedicine area.
Keywords: Smart nanocarriers